The Effects of Extracurricular Activities on Developing Students’ Life Skills - Saki , Ousama; Darhour, Hanane (International Journal of Language and Literary Studies, 2023)
This study explores the views of teachers and students regarding the effect of extracurricular activities on the development of life skills for Moroccan high school students. To achieve this objective, the study uses a convergent parallel mixed-methods design and adopts UNICEF’s Life Skills and Citizenship Education Conceptual and Programmatic Framework (2017). The study collected quantitative data from 257 public high school students and 68 public high school teachers through anonymous surveys. Qualitative data were collected from 47 students and 16 teachers through focus groups. Quantitative data were analysed statistically using SPSS Version 20, while qualitative data were analysed thematically. The overall results reveal that extracurricular activities promote life skills almost moderately, though it is often unintentional. The study concludes with some recommendations for education stakeholders on how to use extracurriculars to promote life skills for Moroccan high school students.